2023
DOI: 10.3390/healthcare11060808
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Knowledge about Fang Traditional Medicine: An Informal Health Seeking Behaviour for Medical or Cultural Afflictions in Equatorial Guinea

Abstract: This study explores a range of informal health-seeking behaviors, including the use of Fang Traditional Medicine (FTM) for medical or cultural afflictions in Equatorial Guinea (EQ), the therapeutic methods used, the health problems handled, the learning process, traditional medicine user profiles and the social images of Fang Traditional Healers (FTHs). Ethnography was employed as a qualitative strategy using emic–etic approaches. Semi-structured interviews were conducted with 45 individuals, including 6 commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…31 Equatorial Guinea has health workforce shortages, with 2017 data showing four doctors per 10,000 inhabitants. 32 The country has seen recent economic declines, resulting from drops in oil prices and the effects of the COVID-19 pandemic. These are likely to have negatively affected investments in the health system.…”
Section: Health System In Equatorial Guineamentioning
confidence: 99%
See 1 more Smart Citation
“…31 Equatorial Guinea has health workforce shortages, with 2017 data showing four doctors per 10,000 inhabitants. 32 The country has seen recent economic declines, resulting from drops in oil prices and the effects of the COVID-19 pandemic. These are likely to have negatively affected investments in the health system.…”
Section: Health System In Equatorial Guineamentioning
confidence: 99%
“…35,36 One study on the use of traditional medicine in Equatorial Guinea found that while people might seek traditional medicine for 'ordinary' febrile diseases like malaria, the standing of traditional healers has declined, and many Guineans expressed limited confidence in their ability to heal disease. 32…”
Section: Health System In Equatorial Guineamentioning
confidence: 99%
“…The recent literature on traditional medicine is mainly focused on the knowledge of experienced practitioners or healers, whereas domestic medicine research focused on the users knowledge, such as the skills and cultural beliefs of women, is rather scarce ( Choudhry, 1997 ; Cabré, 2008 ), although it is well documented that women and elders are the most active consumers of traditional medicine ( Voeks, 2007 ; Schunko et al, 2012 ; Jimenez-Fernandez et al, 2023 ). Women were also related to collecting and drying herbs as a source of botanical drugs (Ishtiaq et al, 2022), as well as to plant preservation efforts ( Bowcutt and Caulkins, 2020 ).…”
Section: Introductionmentioning
confidence: 99%